Factors Influencing the Efficacy of Agile Usage - Shahzeb Hussain; Namrata Bhadri; Syed Razauddin Shahlal (International Journal of Engineering and Management Research, 2020)
Agile techniques that utilize iterative development are broadly used in various industry projects as a lightweight development technique which can satisfy the continuous changes of requirements. Short repetitions are used that are required for efficient product delivery. Traditional and old software development methods are not much efficient and effective to control the rapid change in requirements. Despite the benefits of Agile, criticism on agile methodology states that it couldn’t succeed to pay attention to architectural and design issues and therefore is bound to produce small design-decisions. The past decade has observed numerous changes in systems development with many organizations accepting agile techniques as a viable methodology for developing systems. An increase in the number of research studies reveals the growing demand and acceptance of agile methodologies. While most research has focused on acceptance rate and adaptation of agile practices, there is very limited knowledge of their post-adoption usage and incorporation within organizations. Several factors explain the effective usage of agile methodologies. A combination of previous research in Agile Methodologies, Diffusion of Innovations, Information Systems implementation, and Systems Development has been carried out to develop a research model that identifies the main factors relevant to the propagation and effective usage of agile methodologies in organizations.